Penetration trajectory planning based on radar tracking features for UAV - Chen, Shaofei; Liu, Hongfu; Chen, Jing; Shen, Lincheng (Aircraft Engineering, 2013)
Purpose - The purpose of this paper is to plan the penetration trajectory for unmanned aerial vehicle (UAV) in the presence of radar-guided surface to air missiles (SAMs).Design methodology approach - The penetration trajectory planning problem is modelled based on four aspects of radar tracking features. As penetration just utilizes the low observability of radar cross section (RCS) to satisfy temporal constraints of tracking, the problem is formulated as multi-phase trajectory planning with detected probability (MTP-DP). While utilizing both the low observability of RCS and the radial velocity blind area of radar, the problem is formulated as multi-phase trajectory planning with detected probability and radial velocity (MTP-DP&RV). The pseudospectral multi-phase optimal control based trajectory planning algorithm is proposed.Findings - The results of the examples illustrate that the multi-phase trajectory planning method can finely utilize the radar tracking features to optimize the comprehensive efficiency of penetration. The pseudospectral multi-phase optimal control based trajectory planning algorithm could effectively solve the trajectory planning problem.Originality value - This paper provides new structured method to plan UAV penetration trajectory for military application and academic study.